Comparison of Burnout Syndrome among Speech Language Pathologists In Clinical and Academics Setup - Tarar, Amna; Khan, Muhammad Azzam; Saeed, Bareera; Khan, Sikander Ghayas; Ikram, Atif; Naeem, Usra; Malik, Munawar Ahmed; Ahmad, Muhammad (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
Background: Speech-language pathologists being the important component of the health care professionals are vulnerable to Burnout syndrome. This generated a necessity to come up with approaches to eradicate this burnout by providing compensations from the organizations and taking care of the well being, job satisfaction of the speech-language pathologists Objective(s): To assess the extent of Burnout syndrome among Speech-language pathologists in clinical and academic setup. Methodology: To assess comparison, a comparative cross-sectional study was held in which speech-language pathologists (n= 143) completed an online survey with 30 questions related to Burnout. A customized questionnaire was developed with the help of expert opinion and literature review as there no standardized questionnaire for Comparison of Burnout syndrome to asked retrospective ratings of the participants. Measures of ratings included custom-made attitudinal statements towards Burnout syndrome by Speech-language pathologists. Results: The outcome demonstrates that 56.5% of Speech-language pathologists experience Burnout which suggests that there’s no substantial Burnout among Speech-language pathologists in clinical and academic setup. Conclusion(s): Job contentment, pressure, and burnout were found to be attributed to several occupational aspects, comprising components of need, assistance, and reward. No prior surveys have analyzed the interaction between various components of a job, which might increase satisfaction or alleviate tension in SLPs. This is the first study using a comparative cross-sectional approach to concentrate on well-being, satisfaction, burden, and burnout in SLPs and infers more endeavor needs to be performed to improve observe and promote the well-being of the workforce.